2000
DOI: 10.1152/ajpendo.2000.278.2.e273
|View full text |Cite
|
Sign up to set email alerts
|

Combined effects of hyperaminoacidemia and oxandrolone on skeletal muscle protein synthesis

Abstract: We investigated whether the normal anabolic effects of acute hyperaminoacidemia were maintained after 5 days of oxandrolone (Oxandrin, Ox)-induced anabolism. Five healthy men [22 +/- 3 (SD) yr] were studied before and after 5 days of oral Ox (15 mg/day). In each study, a 5-h basal period was followed by a 3-h primed-continuous infusion of a commercial amino acid mixture (10% Travasol). Stable isotopic data from blood and muscle sampling were analyzed using a three-compartment model to calculate muscle protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 21 publications
0
27
0
Order By: Relevance
“…Insight into how oxandrolone may exert its effects may be found in a study by Sheffield-Moore et al 19 In their study, which used stable isotopes to assess protein metabolism, they found that in young men, oxandrolone significantly increased the fractional synthetic rate without an increase in muscle protein breakdown, resulting in a positive net protein balance, as well as an improved intracellular use of amino acids. In addition, their study found a significant increase in the number of androgen receptors, through which anabolic agents translate their action.…”
Section: Discussionmentioning
confidence: 99%
“…Insight into how oxandrolone may exert its effects may be found in a study by Sheffield-Moore et al 19 In their study, which used stable isotopes to assess protein metabolism, they found that in young men, oxandrolone significantly increased the fractional synthetic rate without an increase in muscle protein breakdown, resulting in a positive net protein balance, as well as an improved intracellular use of amino acids. In addition, their study found a significant increase in the number of androgen receptors, through which anabolic agents translate their action.…”
Section: Discussionmentioning
confidence: 99%
“…A second catheter was placed in a dorsal hand vein, and the hand was heated to obtain arterialized blood samples (1). After collection of basal measures (protein synthesis and signaling), a primed, continuous infusion of unlabeled amino acids (10% Travasol; Clintec Nutrition, Deerfield, IL) was initiated (8,16,41) and continued for 3 h (Fig. 1).…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, after repeated bouts of RE it is possible that there is a lower net accumulation of new muscle protein and a reduced ability to maintain or increase muscle mass in the soleus. Collectively, these results indicate a muscle-specific (vastus lateralis vs. soleus) protein metabolic response to disuse and RE and highlight the need for the development of muscle-specific countermeasures to muscle atrophy.Because amino acids have been shown to stimulate vastus lateralis protein synthesis to a similar extent as seen with RE (8,35,41), they may provide an additional means of elevating protein synthesis in the soleus and stimulating muscle growth during unloading. However, the response to supplemental amino acids has not been studied in the soleus muscle, and it is unclear how the soleus will respond to nutritional stimulation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…New advances in synthetic hormones provide promise for expanded applications in the future. For example, the synthetic steroid oxandralone stimulates muscle growth, possibly without the same magnitude of androgenizing effects of testosterone (55). At the same time, there are limits and dangers of hormonal therapy caused by unexpected, unwanted, and often unrecognized complications.…”
Section: Hormonal Therapymentioning
confidence: 99%